Investigating Bodily Injury - Endre Nyitrai; Kornel Girhiny; Laszlo Boi; Henrietta Farkasne dr. Halasz; Orsolya Haspel (European Scientific Journal, ESJ, 2022)
This study shall analyse the statutory provisions on bodily injuries or batteries with a special outlook on the difficulties caused by the pandemic. The study formulates forensic recommendations based on the Hungarian national standard and knowledge of criminal procedure and analyzes the methodology of the investigation of bodily harm exclusively from the Hungarian point of view. It approaches the detection of the crime from a practical and empirical point of view, as well as from a legal point of view. The study shall introduce the relations of corona virus and HIV virus to bodily injuries. Interpretation of the recommendations of criminalistics is indispensable for the detection of bodily injuries, similarly, the identification of the methods revealing criminal actions and the questions to be asked during the interrogation of the suspect are also absolute necessities in the process.